2007
DOI: 10.1080/01421590701378662
|View full text |Cite
|
Sign up to set email alerts
|

Use of interactive theater for faculty development in multicultural medical education

Abstract: A workshop using interactive theater was effective in training faculty to facilitate small-group discussions about multicultural issues. This approach emphasizes and models the need to foster critical consciousness in medical education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
45
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 17 publications
1
45
0
Order By: Relevance
“…A variety of faculty development efforts including incorporation of interactive theater techniques by one institution helped increase faculty capacity to facilitate potentially challenging discussions on diversity and social justice issues with students. 9 Boscardin et al 10 also found positive change in student attitudes' towards working with underserved populations with increased experience in competency training and community field work experiences.…”
Section: ) Increase Opportunities For Positive Interactionmentioning
confidence: 96%
“…A variety of faculty development efforts including incorporation of interactive theater techniques by one institution helped increase faculty capacity to facilitate potentially challenging discussions on diversity and social justice issues with students. 9 Boscardin et al 10 also found positive change in student attitudes' towards working with underserved populations with increased experience in competency training and community field work experiences.…”
Section: ) Increase Opportunities For Positive Interactionmentioning
confidence: 96%
“…We have used a similar approach in faculty development and learning experiences to stimulate critical discussions on race, ethnicity, gender, sexual orientation, and socioeconomic class. 10,16 The selected scenes are as follows:• Scene 1. (Part 1) An Iranian immigrant and his daughter are seeking to purchase a firearm from a Caucasian pawnshop owner.…”
mentioning
confidence: 99%
“…The University of Michigan Medical School has implemented a critical consciousness-based curriculum for medical students since 2003 [38][39][40][41][42][43]. Such an exercise can be used to gather evidence for the influence of training on how the physicians will properly perform PSSU.…”
Section: Critical Consciousnessmentioning
confidence: 99%